Alpha-Amylase Activity in Blood Increases after Pharmacological, But Not Psychological, Activation of the Adrenergic System. - Urs M Nater; Roberto La Marca; Katja Erni; Ulrike Ehlert (PLoS ONE, 2015)
Alpha-amylase in both blood and saliva has been used as a diagnostic parameter. While studies examining alpha-amylase activity in saliva have shown that it is sensitive to physiological and psychological challenge of the adrenergic system, no challenge studies have attempted to elucidate the role of the adrenergic system in alpha-amylase activity in blood. We set out to examine the impact of psychological and pharmacological challenge on alpha-amylase in blood in two separate studies.In study 1, healthy subjects were examined in a placebo-controlled, double-blind paradigm using yohimbine, an alpha2-adrenergic antagonist. In study 2, subjects were examined in a standardized rest-controlled psychosocial stress protocol. Alpha-amylase activity in blood was repeatedly measured in both studies.Results of study 1 showed that alpha-amylase in blood is subject to stronger increases after injection of yohimbine compared to placebo. In study 2, results showed that there was no significant effect of psychological stress compared to rest.Alpha-amylase in blood increases after pharmacological activation of the adrenergic pathways suggesting that sympathetic receptors are responsible for these changes. Psychological stress, however, does not seem to have an impact on alpha-amylase in blood. Our findings provide insight into the mechanisms underlying activity changes in alpha-amylase in blood in healthy individuals.